Pressezensur in der ersten Hälfte des 19. Jahrhunderts in Danzig - Chojnacka, Małgorzata (Studia Germanica Posnaniensia, 2018)
In Danzig the magazines had to fight hard to survive. The city was in a very bad economic condition in that period, and there was also a strong stagnation in the culture. According to them, the interests with the newspapers and magazines was very small at the beginning, the periodicals which were coming into being, were being closed very soon, the censors didn't have much work to do, so that they even didn't need special instructions at all. Just in the 20ties and 30ties there are more new magazines turning up and according to them troubles and conflicts with the censorship. The Danzig editors fighted for imprimatur, tried to smuggle into their magazines political opinions, critical comments, uncommon articles; the first discussions in the press turned up. As an answer to this the Danzig magazines and their editors learnt by experience every restriction of the Prussian censor: intervenses in the contents, confiscations, prohibitions, penalties, fines and imprisonment. Never the less they became during this process of the fightening against the censorship more mature in political meaning as well as in journalistic sense.